Vigor de sementes de soja: caracteres de raízes, crescimento vegetativo e rendimento de grãos - Ebone, Luciano Antônio (2020)
Despite being the main legume cultivated in the world, soybean [Glycine max (L.) Merrill] presents several gaps in the knowledge about its cultivation. One of the main gaps of the crop are the impacts of seed vigor on the development of the crop and which are the characters of the roots that are responsible for the differences in yields between plants of the same genotype. Two experiments were developed, the first determined the impacts of seed vigor on uniformity and growth, as well as on the development and productivity of soybean plants. The treatments consisted of four vigor levels (89, 57, 47 and 43%) obtained by accelerated aging (32°C and 95% relative humidity for 0, 120, 192, e 216 h) the seeds, in a randomized block design, with five replications in three locations in the municipalities of Coxilha (Site I) and Passo Fundo (Sites II and III). The second experiment, on the other hand, aimed to investigate whether different classes of soybean grain yield grown in different locations interfere with the morphology of the root system, as analyzed by the WinRHIZO® software. The soybean cultivar DM 5958 RSF IPRO was used in a completely randomized design, which consisted of forty replicates and five treatments. The treatments consisted of three cultivation sites (I, II and III) and five soybean grain productivity classes (C1, C2, C3, C4 and C5). Plant emergence and root system morphology were evaluated. Seeds with a higher level of vigor showed greater uniformity and faster emergence. The unevenness caused by differences in vigor in emergence creates dominant and dominated plants, and the plants dominated through their phenotypic plasticity modify the stem diameter and the length of the internodes to match their height with the dominant plants. The plants that emerged first had a larger leaf area in the three stages (V1, V4 and R2), allowing them to accumulate more photoassimilates in the initial stages. Consequently, these plants exhibited an increase in production components, especially the number of fertile nodes and the number of pods per plant, making them more productive. The results of the second experiment showed that plants with higher grain yield - class C1 - needed less time to emerge and that plants with lower grain yield - class C5 - required more time. Soybean plants with higher grain yield - class C1 - showed a longer total root length, larger amount of very thin roots, thin roots, thick roots and forks and a higher root volume. There was a positive association between all root variables and productivity per plant, and the generic dissimilarity dendrogram between the five classes (C1-C5) formed two distinct groups. In this regard, the main attributes responsible for the segregation of soybean plants in the grain production classes were the volume and length of the thick roots.